JEWISH ANTAGONISM AS PORTRAYED BY HAMKA IN THE BOOK OF TAFSIR AL-AZHAR - Muhammad, Muhammad; Mahmudi, Zaenul; Hamdan, Ali; S Alahmadi, Fahd Mohana; Rusdi, Mikdar (Universitas Islam Negeri Ar-Raniry, 2024)
Abdul Malik Karim Amrullah (Hamka) is widely recognized as a leading Muslim intellectual of 20th-century Indonesia, renowned for his extensive body of work, including both novels and Qur'anic exegesis. His tafsir has been the subject of considerable scholarly interest across Asia. The Qur'an contains numerous verses concerning the Jews, and as an exegete of the entire 30 juz of the Qur'an, Hamka offers a distinct interpretation of these verses. The 20th century was a period marked by significant global political upheaval, notably the establishment of Israel in 1948. The creation of the Israeli state had profound consequences for Muslims worldwide, intensifying anti-Jewish, anti-Zionist, and anti-Israel sentiments, which also permeated discourse in the United States and the United Kingdom. Within this context, several Islamic scholars began to integrate European concepts found in the